Sosialisasi Kesehatan Cegah Stunting dan Gizi Buruk Pada Ibu Hamil dan Baduta di Kelurahan Tanjung Jaya Kota Bengkulu - Dri Asmawanti-S; Novita Sari; Vika Fitranita; Wahyu Satria Hidayat (Kreativasi : Journal of Community Empowerment, 2022)
Community service is a form of student service to the community. At the same time as part of the implementation of the Tri Dharma of Higher Education. One of the work programs in this service is the Health Socialization to Prevent Stunting and Malnutrition for Pregnant Women and Baby less than 2 Years in Tanjung Jaya. This socialization activity was carried out to increase the knowledge and understanding of the people of in Tanjung Jaya regarding stunting prevention. This activity is carried out by the method of direct implementation to the community. The results of this socialization activity are expected to be able to provide an understanding of the dangers of stunting and malnutrition in pregnant women and baby less than 2 years so that they can try to prevent them as early as possible.